(untitled) (Health Renaissance, 2012)
Ganglioneuromas are fully differentiated benign tumors of the sympathetic nervous system arising from the neuroectodermal cells. Its reported incidence is one per million populations. We report an incidentally detected, histopathologically proven ganglioneuroma of the retroperitoneum in a 39 year old lady with the preoperative diagnosis of adrenal tumor. DOI: http://dx.doi.org/10.3126/hren.v10i2.6586 Health Renaissance 2012; Vol 10 (No.2); 147-149